2021
DOI: 10.11591/ijpeds.v12.i2.pp1102-1113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wind speed characteristics using different distribution models in Medan City, Indonesia

Abstract: <span lang="EN-CA">Estimating wind speed characteristics plays an essential role in designing a wind power plant at a selected location. In this study, the Weibull, gamma, and exponential distribution models were proposed to estimate and analyze the wind speed parameters and distribution functions. Real measured data were collected from Medan City, Indonesia. The scale and shape factors of wind distribution for three years data were calculated. The observed cumulative probability of the three models was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Because of its several advantages, Weibull distribution is the commonly used model [17], [27] for wind speed evaluation and analysis. The mean speed is calculated as [11], [12]:…”
Section: Analysis Of Wind Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its several advantages, Weibull distribution is the commonly used model [17], [27] for wind speed evaluation and analysis. The mean speed is calculated as [11], [12]:…”
Section: Analysis Of Wind Energymentioning
confidence: 99%
“…Hoxha et al [10] has confirmed that the Weibull model is better than rayleigh model in terms of fiting wind speed variation, and this, after a statistical analysis of the wind speed in Kitka followed by a comparative study between the two models. After the study of the wind speed characteristics for Medan City, Indonesia, Suwarno et al [17] has argued that the Weibull model is the better model compared to gamma and exponential distribution models.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in pressure affects the strong and weak wind speeds. According to several previous researchers [1], [2] and others have presented wind speed parameters [3]- [6]. Wind speed characteristics are analyzed in depth to improve the performance of the electricity production in specific locations [7]- [10].…”
Section: Introductionmentioning
confidence: 99%